2014
DOI: 10.1097/ncq.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Sedation in Patients Receiving Opioids for Pain Management

Abstract: Excessive sedation precedes opioid-induced respiratory depression. An evidence-based practice project standardized systematic sedation monitoring by nurses using an opioid sedation scale and respiratory assessment when opioids are administered for pain management. Nurses were educated and documentation updated. Nurses demonstrated increased ability to identify at-risk patients (3.2 pre-implementation; 3.6 post-implementation; 1-4 Likert scale) and reported understanding the tool to assess for oversedation (2.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Despite the use of sedation scales being highly recommended, there is evidence that nurses are not convinced that their use has decreased opioid-related adverse events (Davis et al, 2017). There is also little evidence substantiating how nurses incorporate measuring sedation into their critical decision-making pathway to determine if it is safe to administer another dose of opioid or other sedating medication (Lee et al, 2015;Smith, Farrington, & Matthews, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the use of sedation scales being highly recommended, there is evidence that nurses are not convinced that their use has decreased opioid-related adverse events (Davis et al, 2017). There is also little evidence substantiating how nurses incorporate measuring sedation into their critical decision-making pathway to determine if it is safe to administer another dose of opioid or other sedating medication (Lee et al, 2015;Smith, Farrington, & Matthews, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several sedation scales in clinical use, the POSS was the only tool found that guided nurses in the decision to medicate with opioids for acute pain (Davis et al, 2017;Nisbet & Mooney-Cotter, 2009). As reported in the literature, nurses who used the POSS reported a small increase in comfort with ensuring safe administration of opioid medications (Smith et al, 2014). Additionally, the American Society of Pain Management Nurses practice survey also reported that nurses were not convinced that using a sedation scale was useful (Jungquist et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The POSS has been shown to generate consistent assessments and had high levels of user satisfaction in several studies. [12][13][14][15] The tool was developed specifically for opioid sedation monitoring and incorporating specific action steps for nurses to follow when a certain sedation level is observed. The POSS also increased the amount of dialogue about sedation during interdisciplinary rounds and was included in shift-to-shift nursing handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent agreement among published guidelines that the frequency, intensity, and duration of monitoring should be based on the type of opioid therapy, patient risk factors, and response to treatment; and that current nursing assessments every 4 hours may not be adequate for early detection of opioid-induced adverse events. In one study instituting increased nursing assessments (every 1 hour for 12 hours, then every 2 hours for 12 hours) and the Pasero Opioid-Induced Sedation Scale, the facility documented no adverse opioid-related events after the policy was effectively instituted (Smith, Farrington, & Matthews, 2014).…”
Section: Recommendationmentioning
confidence: 99%
“…Growing evidence indicates the value of using reliable and valid sedation scales to quantify and describe opioid-induced sedation (Dunwoody & Jungquist, 2018). Sedation or altered level of consciousness is a common effect of opioids, and unintended advancing sedation is a serious adverse event that often precedes opioid-induced respiratory depression (Ghelardini, Di Cesare Mannelli, & Bianchi, 2015;ISMP, 2013;Macintyre, Loadsman, & Scott, 2011;Motov, Rosenbaum, Vilke, & Nakajima, 2016;Oosten et al, 2011;Smith et al, 2014;Yamamotova, Fricova, Rokyta, & Slamberova, 2016). Clinicians continue to emphasize the importance of routine assessments of sedation levels as part of monitoring practices for opioid-related adverse events (Dalton et al, 2001;Gordon, Pellino, Higgins, Pasero, & Murphy-Ende, 2008;Hayes & Gordon, 2015;Jarzyna et al, 2011;Pasero, 2009).…”
Section: Recommendationmentioning
confidence: 99%